Multilevel Analysis on the Socio-Cultural, Lifestyle Factors, and School Environment on the Risk of Overweight in Adolescents, Karanganyar District, Central Java - Aris Widiyanto; Bhisma Murti; RB. Soemanto (Journal of Epidemiology and Public Health, 2018)
Background: Basic Health Research (RISKESDAS) data in 2013 showed that the prevalence of overweight among adolescents aged 13-15 years was 10.8%. Karanganyar district is ranked fourth by the number of overweight adolescents cases in Central Java with prevalence of 8.2%. This study aimed to determine the asssociation between socio-cultural, lifestyle factors, and school environment on the risk of overweight in adolescents, Karanganyar District, Central Java, using social cognitive theory (SCT), PRECEDE-PROCEED model, and multilevel analysis.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted at 25 junior high schools in Karanganyar district, Central Java, in December 2017. A sample of 200 junior high school students were selected for this study by stratified sampling and fixed disease sampling. The dependent variable was overweight. The independent variables were nutritional intake, snacking habits, physical activity, self efficacy, paternal BMI, maternal BMI, peer group influence, and school environment. Body weight data was measured by digital scale. Contextual effect of school environment was measured by the number of snack sellers at school. Other data were collected by questionnaire and analyzed by multilevel analysis.Results: High nutritional intake (b= 1.56, SE = 0.73, p= 0.032), high snacking habits (b= 1.27, SE = 0.70; p= 0.069), paternal BMI ≥23 (b= 1.60; SE= 0.79; p= 0.042 ), maternal BMI ≥23 (b= 2.29; SE = 0.76; p = 0.002), parent income ≥minimum  regional  wage (b= 2.17; SE= 0.76; p= 0.004), and strong peer group influence (b= 2.22; SE = 0.65; p= 0.001) increased the risk of overweight in adolescents. High self-efficacy (b= -3.61, SE= 0.75, p <0.001) and high physical activity (b= -2.92; SE= 0.80; p <0.001) decreased the risk of overweight in adolescents. Intraclass correlation= 9.92% indicating considerable contextual effect of school environment.Conclusion: Nutritional intake, snack habits, paternal BMI, maternal BMI, family income, and peer influence increase the risk of overweight in adolescent. Self-efficacy and high physical activity decrease the risk of overweight in adolescent. School environment has a considerable contextual effect on overweight in adolescents.Keyword: overweight, social cultural factor, adolescents, school environmentCorrespondence: Aris Widiyanto. School of Health Sciences Mambaul Ulum, Jl. Ring Road Utara, Tawangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: widiyanto.aris99@gmail.com. Mobile: 081329209095.Journal of Epidemiology and Public Health (2018), 3(1): 94-104https://doi.org/10.26911/jepublichealth.2018.03.01.08